ANALISIS LAPORAN KEUANGAN SEBAGAI BAHAN PERTIMBANGANPEMBERIAN KREDIT (Studi Pada Lembaga Keuangan Di Kota Malang) - Wahyuni, Nanik (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
This research aims to determine the the basis of valuation and credit analysis in the loan application process on the existing financial institutions in the city of Malang. In addition, provide the evidence that the financial statements have a very important role in the mortgage application process on the existing financial institutions in the city of Malang. The researchÂ used a quantitative research study in financial management that analyzed the financial statements of the debtor with the status of legal entities that are used in the provision of credit to financial institutions in the city of Malang. Data analysis techniques use ratio analysis, comparative analysis of financial statements, common size analysis.